Structural and Ph sensing properties of spin coated Tio₂ thin films with varied sol-gel concentration and with different composite bilayer configuration / Rohanieza Abdul Rahman ...[et al.] - Abdul Rahman, Rohanieza; Yusof, Khairul Aimi; Zulkefle, Muhammad Al Hadi; Abdullah, Wan Fazlida Hanim; Kamarudin, Yusuf (Universiti Teknologi MARA, 2019)
Sol-gel spin coated titanium dioxide (TiO2) was applied as the sensing membrane for extended gate field effect transistor (EGFET) pH sensor. The molarity of the TiO2 sol-gel was manipulated to study its influence on the film pH sensing capability. In this study, the sol-gel solution concentration was varied from 0.2 M to 1.0 M. It was observed that an increase in molarity used would results in the decrease of pH sensitivity of the TiO2 thin film, in which, the highest pH sensitivity (42.60 mV/pH) was obtained from the film deposited using the lowest concentration. As sol-gel concentration becomes higher, the films becomes thicker, deteriorating its pH sensing performance. FESEM images showed that the variation of the sol-gel concentration influenced the surface morphology. XRD results obtained confirmed the anatase phase existence in all TiO2 samples, excluding that of 0.2 M sample that was amorphous with no peaks. Besides that, composite bilayer sensing structure obtained by incorporating ZnO with TiO2 thin film can produce sensing membrane with higher pH sensitivity than a pure TiO2 sensing membrane. The sensitivity value for TiO2/ZnO and ZnO/TiO2 composite bilayer samples are 57.1 mV/pH and 46.9 mV/pH respectively.